2021
DOI: 10.1177/1078087421992879
|View full text |Cite
|
Sign up to set email alerts
|

Women and Local Politics: Determinants of Women’s Emergence and Success in Elections to Czech Town Councils, 1998–2018

Abstract: The main objective of this paper is to analyse where women run for and win seats in local councils of Czech towns between 1998 and 2018. Our results are to some extent contradictory to those from Western Europe. More importantly, this study demonstrates that strategic context impacts on women’s emergence and success in local elections in a different way. First, we do not confirm that larger towns are more promising for women’s representation. While more fragmented party systems in larger cities contribute to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
1
4
1
Order By: Relevance
“…As explained in the methods section, both were intended to assess the influence of previous female leadership, a factor that has become consolidated in the territories as an element that favours greater female access to local government. The results of our analysis were once again negative, in contrast to comparable studies (Maškarinec 2022;Crowder-Meyer et al, 2015), since neither of the two bivariate spatial correlations carried out (female councillors 2007/ female councillors 2015; % female councillors 2015/ presence of female mayors 2019) yielded significant data (Maps 15 to 18; Figures 7 and 8). Several studies have also reported significant regional variation in other countries, evidence that may prompt scholars to explore the implications of local non-partisanship (Smith et al, 2012).…”
Section: Annual Growth (%) Female Mayorscontrasting
confidence: 88%
See 3 more Smart Citations
“…As explained in the methods section, both were intended to assess the influence of previous female leadership, a factor that has become consolidated in the territories as an element that favours greater female access to local government. The results of our analysis were once again negative, in contrast to comparable studies (Maškarinec 2022;Crowder-Meyer et al, 2015), since neither of the two bivariate spatial correlations carried out (female councillors 2007/ female councillors 2015; % female councillors 2015/ presence of female mayors 2019) yielded significant data (Maps 15 to 18; Figures 7 and 8). Several studies have also reported significant regional variation in other countries, evidence that may prompt scholars to explore the implications of local non-partisanship (Smith et al, 2012).…”
Section: Annual Growth (%) Female Mayorscontrasting
confidence: 88%
“…In contrast, we obtained a low level of significance for female mayors, as shown in the cluster map (Map 7) and in the significance map (Map 8), with a spatial correlation of only 0.0012. The findings for Spain follow a similar pattern to those reported in a recent study on the Czech Republic (Maškarinec 2020;2022), and our research also has policy implications since it demonstrates that the degree of women's political representation is a highly endogenous phenomenon whose reproduction depends on the particular actors and factors that exist within the space of individual municipalities.…”
Section: Annual Growth (%) Female Mayorssupporting
confidence: 88%
See 2 more Smart Citations
“…This means that the pipeline to politics excludes in a more subtle way than formal exclusion once did (Phillips, 1995). Members of minority groups have less access to networks, funding, and experience, and are seen as less viable candidates by the establishment and even themselves (Lawless and Fox, 2005;Folke and Rickne, 2016;Maškarinec, 2021). Although women have increased their numbers in areas generally considered as pathways to politics, such as law, and accrue more years of formal education than men in most countries (Gomes, 2012), they are still less likely to be active party members, achieve leadership positions within parties, or become candidates.…”
Section: Understanding the Pipeline To Institutional Politicsmentioning
confidence: 99%